Synthesis of new substituted 7,12-dihydro-6,12-methanodibenzo[c,f]azocine-5-carboxylic acids containing a tetracyclic tetrahydroisoquinoline core structure - Grajewska, Agnieszka; Chrzanowska, Maria; Adamska, Wiktoria (Beilstein Journal of Organic Chemistry, 2021)
A convenient and simple protocol has been developed for the synthesis of a series of new tetracyclic tetrahydroisoquinoline derivatives, 7,12-dihydro-6,12-methanodibenzo[c,f]-azocine-5-carboxylic acids by three component Petasis reaction with the use of aminoacetaldehyde acetals bearing substituted benzyl groups as the amine components followed by Pomeranz–Fritsch double cyclization reaction. By applying this method, several acids have been prepared in satisfactory yields. An unprecedented chemical behavior of a Petasis reaction product in diluted HCl solution leading to the formation of a phenylglycine derivative has been observed and the mechanism explaining such reactivity has been proposed.
Keywords: amino acids; cyclization; multicomponent reactions; synthetic methods; tetrahydroisoquinoline